Do Women Choose Different Jobs from Men? Mechanisms of Application Segregation in the Market for Managerial Workers - Barbulescu, Roxana; Bidwell, Matthew (Organization Science, 2013)
This paper examines differences in the jobs for which men and women apply in order to better understand gender segregation in managerial jobs. We develop and test an integrative theory of why women might apply to different jobs than men. We note that constraints based on gender role socialization may affect three determinants of job applications: how individuals evaluate the rewards provided by different jobs, whether they identify with those jobs, and whether they believe that their applications will be successful. We then develop hypotheses about the role of each of these decision factors in mediating gender differences in job applications. We test these hypotheses using the first direct comparison of how similarly qualified men and women apply to jobs, based on data on the job searches of MBA students. Our findings indicate that women are less likely than men to apply to finance and consulting jobs and are more likely to apply to general management positions. These differences are partly explained by women’s preference for jobs with better anticipated work–life balance, their lower identification with stereotypically masculine jobs, and their lower expectations of job offer success in such stereotypically masculine jobs. We find no evidence that women are less likely to receive job offers in any of the fields studied. These results point to some of the ways in which gender differences can become entrenched through the long-term expectations and assumptions that job candidates carry with them into the application process.